Effect of landscape attributes on the occurrence of the endangered golden-headed lion tamarin in southern Bahia, Brazil - Teixeira, Joanison Vicente dos Santos (2024)
The golden-headed lion tamarin (Leontopithecus chrysomelas) is an endangered primate that occurs exclusively in the Atlantic Forest of southern Bahia, Brazil. Its geographic range has been severely reduced by deforestation and its populations are restricted to a human-modified landscape consisting primarily of Atlantic forest fragments and shade cacao (Theobroma cacao) agroforestry, locally known as cabrucas. In the last 30 years, there has been a 42% reduction in the geographic range and a 60% reduction in the population size of L. chrysomelas, with only 8% of its habitat represented by protected areas. Thus, we investigated the occurrence of L. chrysomelas in forest fragments and cabrucas based on interviews and using playback census, and evaluated the influence of landscape attributes on its occurrence. The occurrence was measured using a Generalized Linear Model using a set of 12 predictor variables, including fragment size and elevation. L. chrysomelas inhabited 186 (38%) of the 495 forest fragments and cabrucas. Most inhabited habitat patches (n = 169, 91%) are in the eastern portion (ca. 70 km wide region from the Atlantic coast to inland) of its geographic range. The remaining (n = 17, 9%) are in the western portion of the distribution, between 70 and 150 km from the Atlantic coast. Our models indicate a higher occurrence of L. chrysomelas in the eastern portion of its geographic range, where the landscape exhibits lower land cover diversity, greater functional connectivity, lower altitudes (<400 m), and is primarily composed of forest fragments and cabrucas with a higher core percentage. In contrast, we observed a lower occurrence of L. chrysomelas in the western portion, where the landscape is more diverse and heterogeneous due to anthropogenic activities, such as agriculture and livestock. We urge the establishment of ecological corridors via reforestation of degraded areas in the western portion of the range. This increase in habitat availability and suitability in the west together with the protection of the forests and cabrucas in the east would increase our chances of saving L. chrysomelas from extinction.